Música e deficiência: Processos de ensino e aprendizagem em um espaço não formal de educação musical - Souza, Leonnardo Limongi de (2017)
This research had as objective, understand how occur of the music teaching and learning of the disabled people in a not formal space of special education. By mean of your specific objectives, we look to understand the school’s pedagogical proposal where we did this work; to characterize the pedagogical practices established; identify the of teaching rout training; understand how fathers and teachers understand the actions that are developed in this music education space and identify your objectives together with the practices established. For this, we did use of observations, interviews and document analysis, as a collections tool for a data. The case studied was composed by three teachers, five students and their responsible, involving different modalities of education (violin, cello and musicalization) and situations of different development and learning, with the participation of students with Down Syndrome, intellectual Deficiency and Autism. In our theoretical reference, we search understand about people with deficiency, today and in others history moments, about the different space and possibilities of education this people, as well as the delimitation of the action of special music education. The of data analysis shown us that of the pedagogical actions observed has dialog with the proposal musical education emerged during century XX and the understanding and the respect the human plurality.